Information Systems for Integrated Watershed Management - Qiu, Zeyuan (Annals of Arid Zone, 2016)
Watershed management is a broad concept incorporating plans, policies and activities used to control water and related resources and processes in a given watershed. Watershed management is a decision process that is informed by a combination of biophysical sciences, socio-economic information, and local knowledge. Information systems are the infrastructure and mechanisms that deliver and process watershed information to serve diverse information needs of watershed manager and stakeholders for achieving watershed management goals. Great technological progresses took place in computer and information technologies during the last two decades that can significantly change the ways of delivering and processing the watershed information. This paper reviews the impacts of technological progresses on watershed information delivery and process, various information systems for integrated watershed management, and their current application and future challenges. Five types of information systems for integrated watershed management are reviewed: (i) watershed information clearing house (WIC), (ii) biophysical modeling, (iii) integration of GIS with biophysical models, (iv) spatial decision support system (SDSS), and (v) web-based spatial decision support system (WSDSS). The five information systems represent the wide spectrum of available practices that deliver and process the watershed information. WIC represents the simplest, well-developed information system while WSDSS represents the most complicated, less-developed information system that serves diverse needs in the integrated watershed management process.